r-TOLA: an architecture for real time open learning application for universities - Olanrewaju, Rashidah Funke; Islam, Thouhedul (2014)
Obtaining degree from university requires rigorous findings and research. Some subjects/courses are very challenging that made it essential to form study groups among students. Besides attending regular lectures, it is demanding to manage time for study groups. As a result, most of the time, students perform below expectation in their academic activities. meanwhile, managing a central real time open learning application will help in maintaining group study easily as well as improve students’ academic performance. Hence, this paper proposes a Real Time Open Learning Application for University (r-TOLA) which consists of huge academic study group’s history that will, help students to dig into archives, search case studies, questions, projects and answers. This will also benefit lecturer to know the trend in students’ performance.